Safety and efficacy of hydroxychloroquine for treatment of non‑severe COVID‑19 among adults in Uganda: a randomized open label phase II clinical trial - Byakika‑Kibwika, Pauline; Sekaggya‑Wiltshire, Christine; Semakula, Jerome Roy; Nakibuuka, Jane; Musaazi, Joseph; Kayima, James; Sendagire, Cornelius; Meya, David; Kirenga, Bruce; Nanzigu, Sarah; Kwizera, Arthur; Nakwagala, Fred; et al. (BMC Infectious Diseases, 2021)
Several repurposed drugs such as hydroxychloroquine (HCQ) have been investigated for treatment of COVID-19, but none was confirmed to be efficacious. While in vitro studies have demonstrated antiviral properties of HCQ, data from clinical trials were conflicting regarding its benefit for COVID-19 treatment. Drugs that limit viral replication may be beneficial in the earlier course of the disease thus slowing progression to severe and critical illness. Design: We conducted a randomized open label Phase II clinical trial from October–December 2020. Methods: Patients diagnosed with COVID-19 using RT-PCR were included in the study if they were 18 years and above and had a diagnosis of COVID-19 made in the last 3 days. Patients were randomized in blocks, to receive either HCQ 400 mg twice a day for the first day followed by 200 mg twice daily for the next 4 days plus standard of care (SOC) treatment or SOC treatment alone. SARS COV-2 viral load (CT values) from RT-PCR testing of samples collected using nasal/orapharyngeal swabs was performed at baseline, day 2, 4, 6, 8 and 10. The primary outcome was median time from randomization to SARS COV-2 viral clearance by day 6.
Keywords: COVID-19; Hydroxychloroquine; Outcomes; Treatment; Safety; Efficacy